Remote sensing of vertical phytoplankton pigment distributions in the Baltic: new mathematical expressions. Part 1: Total chlorophyll a distribution - Jerzy Dera; Dariusz Ficek; Bogdan Woźniak; Mirosława Ostrowska; Roman Majchrowski; Joanna Stoń-Egiert (Oceanologia, 2007)
This article is the first in a series of three describing the modelling of the vertical different photosynthetic and photoprotecting phytoplankton pigments concentration distributions in the Baltic and their interrelationsdescribed by the so-called non-photosynthetic pigment factor.The model formulas yielded by this research are an integral part of the algorithms used in the remote sensingof the Baltic ecosystem. Algorithms of this kind have already been developed by our team from data relating mainly to oceanic Case 1 waters (WC1) and have produced good results for these waters. But their application to Baltic waters, i.e.,Case 2 waters, was not so successful. On the basis of empirical data for the Baltic Sea, we therefore derived new mathematical expressions for the spatial distribution of Baltic phytoplankton pigments. They are discussed in this series of articles. This first article presents a statistical model for determining the total concentration ofchlorophyll, a (i.e., the sum of chlorophylls a+pheo derived spectrophotometrically) at different depths in the Baltic Sea Ca(z) on the basis of its surface concentration Ca(0),which can be determined by remote sensing. This model accounts for the principal features of the vertical distributions of chlorophyll concentrations characteristic of the Baltic Sea. The model's precision was verified empirically: it was found suitable for application in the efficient monitoring of the Baltic Sea. The modified mathematical descriptions of the concentrations of accessory pigments (photosynthetic and photoprotecting) in Baltic phytoplankton and selected relationships between them are given in the other two articles in this series (Majchrowski et al. 2007, Woźniak et al. 2007b, both in this volume).